Analisis Harga Pokok Produksi Dengan Metode Activity Based Costing Untuk Mengambil Keputusan Manajemen Pada Industri Garmen CV. Surya Surabaya - Kumalasari, Carolina (Program Doktor Ilmu Ekonomi, 2014)
This study aims to calculate the cost of goods manufactured baby clothes garment CV Surya Surabaya with the ABC method for reporting purposes and objectives of decision making in gaining competitive advantage . Data analysis method used is descriptive analysis method . The results showed that the conventional cost accounting applied in the enterprise value of the difference of the calculation produces the ABC method. Calculation of costs by activity-based costing method is expected to assist management in making more informed decisions as to be benefit/profit. Data collection methods used in this study is documentation . Research subjects in this study is the production cost of baby clothes in CV Surya Garments Surabaya . The research object in this study is the data associated with the determination of the production cost of baby clothes. The difference between the production cost of conventional methods with activity-based costing method produces values undercosting conditions ( conditions in which a product has a lower cost than the actual cost is absorbed by the product ) and overcosting ( a condition in which a product has a higher cost than the cost of which is actually absorbed by the product ). Analysis undertaken in this study members advise the Company to undertake restructuring of the production process and production control for the results of each period more evenly , because the fixed overhead costs is greater than the variable overhead costs , it is most impact in the calculation of the cost of production.Keywords: Conventional Metode, Activity Based Costing Metode, Product costing